Base and wall pressure control using cavities and ribs in suddenly expanded flows -an overview - Sethuraman, Vigneshvaran; Rajendaran, Parvathy; Khan, Sher Afghan (Penerbit Akademia Baru, 2020)
An understanding of fluid flow in sudden expansion has resulted in a great deal of research work in this area. Of particular interest is the study of base drag which influences the performance of automotive vehicles, aircraft, and missiles. Problems of fuel mixing in combustion chambers and reduction of specific fuel consumption are also governed by the phenomenon of base drag. It is the aim of this study to present a brief review of the work carried out in the area of sudden expansion in a duct with particular accent on a few active and passive controls employed to modify the base drag. It is noteworthy that a reduction in base drag is of benefit in combustion mechanisms while an in-crease in base drag is preferred for net drag reduction of bodies moving through air. Suppression of flow oscillations that accompany the control of base drag also merits attention. A few suggestions by way of future work are also discussed.